The Evolving Consumer Behavior: Fan Culture in Online Community - Anindya Widita (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2018)
It is obvious how technology has reformed the way consumers behave. More than influencing factors to buying decision, the study of media consumers has attracted scholars to investigate various subjects related to it. Fan culture has never been this fun back in the days before new media. With the benefit of Internet, fans can be more active in terms of producing and sharing contents and enrich their fan experience. This paper aims to investigate fan practices and experience in an online community as not just media consumers but also producers. The data for this research were collected through one-month online observation in exochocolate LiveJournal community, which is a forum-based community that has been chosen to represent fans in online community. Common practices and characteristics are among the focus chosen to understand the behavior. This research concludes that various content producing and sharing; including the engagement between the fans forms the fan culture in the community. Furthermore, a sense of organization is also seen through how they manage the platform. The shared and common practice such as the style of commenting and the style of organizing the entries or posts are the most apparent examples of the self-organizing community. Fans join the community not only to find information and updates but also to share their opinion and feeling and these contribute to their fan experience because they have other fans to interact with.